2015
DOI: 10.5999/aps.2015.42.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Women Who Have Had Cosmetic Breast Implants That Could Be Associated with Increased Suicide Risk: A Systematic Review, Proposing a Suicide Prevention Model

Abstract: Literature indicates an increased risk of suicide among women who have had cosmetic breast implants. An explanatory model for this association has not been established. Some studies conclude that women with cosmetic breast implants demonstrate some characteristics that are associated with increased suicide risk while others support that the breast augmentation protects from suicide. A systematic review including data collection from January 1961 up to February 2014 was conducted. The results were incorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…Hence, SBI can be considered as trigger of FM [34]. Further, SBI surgery and depression can be stressful events for the patient and can be considered risk factors for suicide [33,34]. In this context, we observed one suicide in our study.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…Hence, SBI can be considered as trigger of FM [34]. Further, SBI surgery and depression can be stressful events for the patient and can be considered risk factors for suicide [33,34]. In this context, we observed one suicide in our study.…”
Section: Resultssupporting
confidence: 48%
“…FM shares some manifestations with ASIA criteria. Factors of atopy and hyperimmune state as well as low levels 5-Hydroxyindoleacetic acid (5-HIAA) a serotonin metabolite have related to ASIA and FM respectively [34]. Other factors have also been implicated, such as surgery for exchange of SBI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, literature indicates an increased risk of suicide among women with breast implants. Indeed, a systematic review of studies addressing cosmetic breast augmentation and suicide concludes a 2–3 times increased risk of suicide for these patients[ 25 ] and this tendency may be explained through the characteristics of the women who are interested in breast augmentation. [ 26 ] Similarly, there is a lot of evidence concerning patients who seek rhinoplasty suggesting that this is a group of patients with a great deal of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Other studies have also found that patients with breast implants underwent breast surgery at a significantly younger age than did breast reduction patients, [29,30] with the typical breast augmentation patient profile being of a young woman aged 28 to 44 years. [31] These differences in age are explained by the fact that most clinical signs for undergoing mastopexy or breast reduction are associated with a series of problems that do not usually appear in younger women, such as sagging breasts due to pregnancy or breast-feeding, hypertrophy after birth or after menopause, and so forth.…”
Section: Discussionmentioning
confidence: 99%